2017
DOI: 10.1103/physrevb.95.205435
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Hall Coulomb drag of massive Dirac fermions

Abstract: Dirac fermions are actively investigated, and the discovery of the quantized anomalous Hall effect of massive Dirac fermions has spurred the promise of low-energy electronics. Some materials hosting Dirac fermions are natural platforms for interlayer coherence effects such as Coulomb drag and exciton condensation. Here we determine the role played by the anomalous Hall effect in Coulomb drag in massive Dirac fermion systems. We focus on topological insulator films with out-of plane magnetizations in both the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 100 publications
1
18
0
Order By: Relevance
“…Weyl fermion semimetals are three-dimensional topological states of matter [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ], in which the conduction and valence bands touch linearly at an even number of nodes, which appear in pairs with opposite chirality. First-principles theoretical studies as well as angle-resolved photo-emission spectroscopy experiments have confirmed the existence of chiral massless Weyl fermions [ 90 ] in topological Dirac semimetals [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ], as well as in type-I [ 107 , 108 , 109 , 110 , 111 ] and type-II [ 112 , 113 , 114 , 115 ] Weyl semimetals (WSM).…”
Section: Introductionmentioning
confidence: 99%
“…Weyl fermion semimetals are three-dimensional topological states of matter [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ], in which the conduction and valence bands touch linearly at an even number of nodes, which appear in pairs with opposite chirality. First-principles theoretical studies as well as angle-resolved photo-emission spectroscopy experiments have confirmed the existence of chiral massless Weyl fermions [ 90 ] in topological Dirac semimetals [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ], as well as in type-I [ 107 , 108 , 109 , 110 , 111 ] and type-II [ 112 , 113 , 114 , 115 ] Weyl semimetals (WSM).…”
Section: Introductionmentioning
confidence: 99%
“…CDWs not aligned with the applied current can be generated in Coulomb-drag setups in the presence of a magnetic field, or if the passive layer is a gapped topological insulator, as a consequence of the (standard or anomalous) Hall drag effect. [26] In any case the CDW appears when the two-dimensional screening length λ = 4πε e 2 ∂µ ∂n (K −1 = n 2 ∂µ/∂n) is negative, which occurs for r s > 2 (see inset of Fig. 1).…”
mentioning
confidence: 97%
“…We have used a general computational scheme and model to describe non-local transport in interactively coupled double layer systems at low temperature and ballistic regime We don't have any experimental and theoretical data corresponding to our system and compare our results theoretically [2,18,19,24,47,49,61] and experimentally with [29] of similar results based on non-homogeneous dielectric environment where. Present approach is based on the Boltzmann kinetic theory, the route to existing formulation to attain the Eq.…”
Section: Resultsmentioning
confidence: 99%
“…mass of electron, dielectric constant of substrate, barrier and air are 13, 4 and 1, respectively. A theoretical calculation have presented to measure the resistivity based on the RPA method at electron density = 2 × 10 11 −2 as RPA method is reliable method for high density regime ≫ 1 [2,24,46,47,61], as shown in Fig. 2, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation